Expandable indexes vs. sequential menus for searching hierarchies on the world wide web - Zaphiris, Panayiotis; Shneiderman, Ben; Norman, Kent L. (My University, 2002)
An experiment is reported that compared expandable indexes providing full menu context with sequential menus providing only partial context. Menu depth was varied using hierarchies of two, three and four levels deep in an asymmetric structure of 457 root level items. Menus were presented on the World Wide Web within a browser. Participants searched for specific targets. Results suggest that reducing the depth of hierarchies improves performance in terms of speed and search efficiency. Surprisingly, expandable indexes resulted in poorer performance with deeper hierarchies than did sequential menus.
Keywords: Information retrieval; menu selection; depth versus breadth in information design; hypertext; web page design; searching; expandable indexes